A study on customers' satisfaction on Petronas gas cylinder as marketed by Petronas Dagangan Bhd In Bintulu / James Untam - Untam, James (2004)
Petronas Dagangan Bhd (PBD) is the principal domestic marketing arm of Petronas, the national company, which hold 69.89% of its equity. Its sales of petroleum product are confined to Malaysia market only and overall market are presently is about 33%: 36% for the LPG. Marketing of Petronas gas cylinder in Bintulu, Sarawak goes back to late 70’s. It was actively involved marketing it cylinder in rural areas, Shell and Esso dominance was challenged which lead to stiff competition among the marketing outfit. Hence, PDB has endeavored to provide premium services to its customers at the most cost effective in order to improve the image and sales of its products. With the listing of PDB in the Kuala Lumpur stock exchange in the 1994, the role played by PDB changed from that of a follower to that of a leader.